Homeland and Alienation in "Shadaia Al Bahr, Hakaya Al Manfa" For the Contemporary Iraqi Poet Jawad Jamil (The International Journal of Educational Sciences and Arts, 2023)
It is no secret to anyone who is familiar with the poetic experience of the contemporary Iraqi poet Jawad Jamil that talking about homeland and exile has a special place in it. And while the love of the homeland is instilled in the instinct of every one of us, and it is from faith, the issue becomes of a distinctive nature when we contemplate it poetically, with a sensitive poet, whose circumstances prescribe him to live in exile from his homeland (Iraq) for many years, during which he suffered great suffering, and he passed Various experiences that had a great impact on his conscience in the beginning, and then on his poetic creativity.This study is an approach to the various artistic images in which the homeland first appeared, in a specific collection of poetry, "Shadaia Al Bahr, Hakaya Al Manfa" as they are multiple images with deep connotations of the features and characteristics of the poet's experience. The study then deals with, after that, the images of alienation from the homeland in the Diwan itself, as this too, with its depth and multiple connotations, reveals complementary dimensions that help clarify the overall picture of the experience. In this endeavor, the study will depend on a descriptive and analytical reading of the aforementioned Diwan. In order for this reading to be our means of entering the poetic world of the poet through his creativity in the Diwan.
Keywords: Homeland; Alienation; Image; Experience; Exile